FAST (Fight Against Stunting Together): Pendekatan Partisipatif melalui Participation Action Research dalam Upaya Penanggulangan Stunting - Tobing, Angga Christopel immanuel Lumbang; Nayoda, Fathan; Hasibuan, Rahmat Dwiki Januarsyah (WISE Pendidikan Indonesia, 2025)
Stunting is a chronic nutritional issue that has long-term impacts on the quality of human resources. In Indonesia, the prevalence of stunting remains high, particularly in rural areas such as Mariana Village, Banyuasin Regency. This study aims to design and implement the Fight Against Stunting Together (FAST) program using a Participation Action Research (PAR) approach, which actively involves the community throughout the planning to evaluation stages. This research is a participatory qualitative study conducted over four months, involving 20 main participants, including posyandu cadres, village officials, and mothers of toddlers. The methods employed include participatory observation, in-depth interviews, and focus group discussions. The findings show that the PAR approach increases community awareness of the importance of nutrition and child-rearing practices, fosters cross-sector collaboration, and leads to local initiatives such as nutrition gardens and mother-toddler education classes. The FAST program has proven effective in fostering a sense of community ownership in stunting prevention efforts and strengthening local capacity to improve child nutrition status. The implications of this study suggest that active community involvement through the PAR model can serve as an effective and sustainable strategy for stunting reduction. Recommendations are offered for replicating similar programs in other areas with adjustments to local contexts and adequate policy support.